HERBACEOUS BIOMASS SHREDDING FOR BIOFUEL COMPOSITIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The 2003 reform o f the EU Common agricultural policy stimulates farmers to grow more energy crops, including short rotation coppice and other perennial crops. Peat can be used as additive for manufacturing o f solid biofuel, because it improves density, durability o f stalk material briquettes (pellets) and avoid corrosion o f boilers. For these reason herbaceous biomass compositions with peat fo r solid biofuel production is recommended. The main conditioning operation before biomass compacting is shredding. It was stated that common reed stalk material particle size reduction during cutting (shredding) process increased energy consumption very significantly. The calculation o f energy consumption fo r common reed cutting to sizes 0.6 and 0.5 mm was giving results 31.3 k J kg'1 and 43.5 k J kg'1. The shredder cutter bar has to be designed with friction energy losses decreased to minimum. This aim can to be realized by reducing o f area o f cutter bar knives moving into stalk biomass and minimizing biomass pressure (Patent LV13447) on cutter bar.